2019
DOI: 10.1001/jama.2019.17021
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Screening for Abdominal Aortic Aneurysm

Abstract: IMPORTANCE Ruptured abdominal aortic aneurysms (AAAs) have mortality estimated at 81%. OBJECTIVE To systematically review the evidence on benefits and harms of AAA screening and small aneurysm treatment to inform the US Preventive Services Task Force. DATA SOURCES MEDLINE, PubMed (publisher supplied only), Database of Abstracts of Reviews of Effects, and Cochrane Central Register of Controlled Trials for relevant English-language studies published through September 2018. Surveillance continued through July 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 121 publications
3
93
0
5
Order By: Relevance
“…Screening can reduce deaths if the people invited participate ( Ronco et al, 2014 , Myers et al, 2015 , National Lung Screening Trial Research Team, 2011 , Lin et al, 2016 , Guirguis-Blake et al, 2019 , Leese et al, 2015 ). Future technological advances will lead to more accurate, and stratified screening tests, offering improvements in early diagnosis and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Screening can reduce deaths if the people invited participate ( Ronco et al, 2014 , Myers et al, 2015 , National Lung Screening Trial Research Team, 2011 , Lin et al, 2016 , Guirguis-Blake et al, 2019 , Leese et al, 2015 ). Future technological advances will lead to more accurate, and stratified screening tests, offering improvements in early diagnosis and survival.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the results of a systematic review study commissioned by the United States Preventive Services Task Force showed that 1-time AAA screening in men 65 years or older was associated with decreased AAA-related mortality and rupture rates and increased rates of elective surgery, but it was not associated with all-cause mortality benefits and long-term differences in the quality of life resulting from screening [ 54 ]. Based on these findings, the said task force recommended 1-time screening for AAA with ultrasonography in men aged 65 to 75 years who have ever smoked and selective screening for AAA with ultrasonography in men aged 65 to 75 years who have never smoked rather than routinely screening all men in this group [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography of the abdominal aorta is a highly sensitive and specific modality for detection of AAAs. 11,27,28 The screening team works at the Department of Vascular Surgery and the Department of Radiology and Interventional Radiology at Oslo University Hospital, and the costs were shared between these two departments. The screening project has no external funding.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9] Several large studies have shown that one-time ultrasound screening in men above 65 years reduces the incidence of sudden AAA ruptures and aneurysm-related mortality. [9][10][11][12][13][14][15] Consequently, Sweden (2006) and the United Kingdom (2009) have implemented national screening programs for ultrasonographic detection of AAA. 9,16 In the United States, one-time screening for AAA has been offered since 2007 to male members of Medicare between the ages of 65 to 75 years with any history of smoking.…”
Section: Introductionmentioning
confidence: 99%